Managerial skills and job performance of librarians : a study on public university libraries in Malaysia - Zalifah binti Awang Zakaria (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
The effectiveness of an organization in achieving its objectives is depending on a proper management of knowledge towards its managerial aspects. However, current studies have shown that an insufficient managerial skill among librarians has contributed to the reduction of job performance. Consequently, the reduction of job performance among librarians leads to the reduction of library's achievement and productivity. In response to this situation, public university libraries have taken the initiative to enhance the skills needed among their librarians. In this study, the managerial skills dimensions that are demonstrated by librarians in the Malaysian public university's library were investigated. This is due to the importance of the public university library as the main entity in supporting the teaching, learning, and research activities at the university. The study was aimed to investigate the managerial skills dimensions and the relationships between these skills and the job performance among Malaysian public university librarians. The managerial skills dimensions; technical, human, and conceptual skills were compared based on the demographics factors of the respondents, including gender, work experience, and position grade. The respondents were selected from ten public university's libraries in Malaysia. These libraries were selected based on the university rank listed by the Ministry of Higher Education in Malaysia. This study employed a quantitative approach, using a structured questionnaire to investigate the managerial skills dimensions and job performance demonstrated by the respondents. A total number of 506 sets of questionnaires were sent out to the targeted respondents and only 415 (82.01%) sets of questionnaires were returned for further analysis. Data were analysed using both SPSS (version 23.0) and Smart PLS (version 3.0) software. The results are presented both in descriptive and inferential statistics. From the findings, human skill was ranked the highest (mean= 5.89), indicating that it was the most preferred skills demonstrated by the respondents. The independent samples t-test comparison analysis revealed that there was a significant difference among respondent's work experience and position grade towards the dimensions of managerial skills except gender. In addition, the findings also revealed that in terms of job performance, contextual performance scored higher (mean= 6.12) than task performance of librarians. The independent samples t-test comparison analysis also indicated that there were significant differences among respondent's gender, work experience and position grade towards job performance. Moreover, the results of the path coefficients indicated that human skills had the highest significant positive effect on job performance, followed by conceptual skills and technical skills for public university librarians. Demographic variables were also found moderating the relationships between technical, human, and conceptual skills and job performance for certain groups. Overall, this study is deemed significant to the field of library and information science practically, theoretically, and methodologically. It helps in determining the current managerial skills among librarians and assessing their proficiency level towards the skills. It provides a guideline for planning, designing, and developing relevant training and development programmes towards upgrading the competency level of librarians and acts as a criterion for the selection and promotion of librarians. Moreover, this study also improved the research instruments and added new knowledge to the library and information science discipline.